A study on depression among caregivers of stroke patients - Abdul Hadi, Azwanis; Pasi, Hafizah; Abd Alla Yousseff, Nivin Essameldin (2016)
ABSTRACT: Introduction: Caregiving for stroke patients is a challenging task both mentally and physically. Studies have shown that caregiving can affect caregivers’ wellbeing that could lead to depression. Objective: This study was carried out to determine the prevalence of depression among caregivers of stroke patients attending Hospital Universiti Sains Malaysia in Kelantan. It is also to evaluate the possible risk factors (patients’ and caregivers sociodemographic data; and caregiver’s burden score) that are associated with depression. Methodology: This is a cross sectional study at the primary care clinic in HUSM in 2013 over a period of 6 months. A total of 116 caregivers of medically documented stroke patients, age more than 18 years and who are able to understand English or Malay were interviewed using the brief patient health questionnaire (PHQ-9) and the Zarit Burden Interview (ZB1). Results: The majority (63.8%) of the caregivers of stroke patients are depressed. Caregiver burden, caregiver’s ethnicity and patient’s ethnicity were found to be significant associated factors for depression. Conclusion: Screening for depression in caregivers especially those with significant factors must be carried out in clinic settings so as to be able to detect and intervene early. Coping mechanisms especially in the religious aspect should be elicited in future studies. KEYWORDS: Caregiver, Depression, Stroke, Malaysia